New data on polymorphism of the meadow spittlebug Philaenus spumarius (L.) (Hemiptera: Aphrophoridae) from the island of São Miguel (Azores) - Borges, Paulo A.v.; Rodrigues, Ana S.b.; Silva, Sara E.; Seabra, Sofia G.; Paulo, Octávio S.; Quartau, José A. (Zootaxa, 2018)
The meadow spittlebug, Philaenus spumarius (L.) (Hemiptera, Aphrophoridae) is a widespread insect species in the Holarctic region, exhibiting a dorsal colour balanced polymorphism. In the Azores the species is known from high elevations in Terceira and São Miguel islands. A sample of 235 individuals from Pico da Vara and Graminhais protected areas (São Miguel, Azores) (between 645 and 935 m a.s.l.), collected in 2000 and 2017, showed a remarkable high frequency of the melanic morphs flavicollis (FLA) and quadrimaculatus (QUA). In addition, a high frequency of melanics was observed in males. We explore the hypotheses for the origin of Azorean colonization and for the high proportion of melanism in the Azorean populations.